PROFILE OF URINALYSIS IN KIDNEY, URETER AND BLADDER STONE PATIENTS - Zamzami, Zuhirman (Indonesian Urological Association, 2019)
Objective: To evaluate the profiles of urinalysis in kidney, ureter, and bladder stone patients. Material & Methods: We reviewed the medical records of kidney, ureter and bladder stone patients proved underwent operative managements and urinalysis in Arifin Achmad Regional General Hospital Pekanbaru Riau Province, Indonesia in 2011-2015. The sampling technique in this study was minimum sampling that meets the inclusion criteria. Univariate test was used for statistical analysis. Approval on the study was obtained from the Ethical Review Board for Medicine and Health Research, Medical Faculty, University of Riau. Results: There were 226 patients fulfilled the inclusion criteria. This study showed that in macroscopic urinalysis the mostly (94.7%) urine density was 1.003-1.030, urine color mostly (46%) was turbid yellow, all (100%) urine acidity showed normal results with mean acidity was 6, most (95.1%) erythrocytes >1 in urine sediment, most (66.2%) leukocytes was >5 hpf, mostly (99.1%) crystal was absent and most urinary epithelium <15 (63.1%). In microscopic urinalysis showed mostly protein in urine was absent (56.4%), and mostly ketone (98.7%) was absent in urine and mostly (56.2%) was absent protein in urine. Conclusion: Urinalysis findings could be normal or abnormal in kidney, ureter and bladder stone patients.